TRA is an Alternative to a TFA for PCI in Patients with ULMCA Stenosis - Vinall, Maria (MD Conference Express, 2011)
Compared with a transfemoral approach (TFA), using a transradial approach (TRA) for unprotected left main coronary artery (ULMCA) disease results in a comparable procedural success rate, a lower rate of vascular complications, similar fluoroscopy time, and shorter hospital stays. TRA should be considered as an alternative to TFA in performing percutaneous coronary intervention for ULMCA diseases.